(3GdhajGJs - (3Jbj GOjf eMeO Hf gLQS Hf QGaYs; (3GdbGSe Hf eMeO Hf jhSa Hf eMeO GHf CHj jOGS GdHQRGdj GdETHjdj Ke GdOeTbj, CHh eMeO, Yde GdOjf,J (B739 (3g` s
(3ChdgG (B:s
(3GeG HYO , aEfi deG QCjJ JGQjN GdMGaX CHj eMeO GdbGSe Hf eMeO GdHQRGdi GfJgi ajg Edi BNQ SfI SJ hKdGKjf hSHYeGFI eHjVG CQOJ Cf CPjd Ydjg s
(3BNQgG (B:s
(3hai jhe GdNejS SGOS YTQi GdTgQ GdePchQ Jhaj Gdabjg GdaGVd GdYGde TeS GdOjf CHhYHOGddg GHf GdWhSi SeY GdbGSe Hf YSGcQ , hSeY efg LeGYI s
(3hGdhajGJ ef SfI (B737 (3g` (B- 773 (3g`s
(3ofbdJ ef NW GdMGaX GHf fGXQ GdOjf hbhHdJ Ydjgs
(3hYdjgG Jedc HGSe eMeO GdCced Hf EHQGgje Hf eadMs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs